A Native‐Chemical‐Ligation‐Based Turn‐on Fluorescent Probe for Selective Detection of Cysteine. Issue 4 (22nd February 2016) - Shimizu, Masaki; Fukui, Hiroki; Shigitani, Ryosuke
Abstract: Selective and quantitative detection of biological thiols such as cysteine, homocysteine, and glutathione is often necessary because abnormal levels of such thiols can cause some diseases. Here, we report that bis(pentafluorophenyl) 1, 4‐benzenedicarbothionic acid diester can serve as a turn‐on fluorescent probe for selective detection of cysteine vis‐a‐vis homocysteine and glutathione. When cysteine was added to a mixture of the diester and a sodium phosphate buffer solution with THF (60 vol%), which is non‐fluorescent, the mixture became green‐fluorescent. In contrast, addition of homocysteine or glutathione did not make the mixture fluorescent. A native‐chemical‐ligation‐based mechanism is proposed. Abstract : Non‐fluorescent 2, 5‐bis(diphenylamino)‐1, 4‐benzenedicarbothioic acid bis(pentafluorophenyl)ester reacts with cysteine and produces a green‐fluorescent amide through native chemical ligation, whereas no fluorescence is observed when the ester is mixed with homocysteine or glutathione. This is the first application of native chemical ligation to selective detection of cysteine (vis‐a‐vis homocysteine and glutathione).